2017
DOI: 10.1364/ome.7.001777
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced periodic surface structures on bismuth thin films with ns laser pulses below ablation threshold

Abstract: We demonstrate the formation of laser-induced periodic surface structures (LIPSS) in bismuth (Bi) thin films by irradiation with nanosecond laser pulses. We report on the formation and the destruction of the LIPSS as a result of the delivered number of pulses; both the formation and destruction threshold were very well determined. Results show that the obtained LIPSS are perpendicular to the laser polarization, and their ripple periodicity is on the order of the irradiation wavelength. Although all the irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…After 90-120 s, the peak of o-BiF 3 disappeared andt wo peaks of metallicb ismuth appeared ( Figure 2f). [24][25][26] The areasofthe two peaks of metallicbismuth after 300-330 sw ere almostt he same as those after 90-120 s, as shown in Figures 2f and 2g.T his experiment was repeated several times and the resultswere always the same. The results indicated that defluorinationo ft he whole surface of an o-BiF 3 particle( or cluster) was almost completed within 120 s. The in- Ramans pectra taken at the position indicated by the blue arrowin(a).…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…After 90-120 s, the peak of o-BiF 3 disappeared andt wo peaks of metallicb ismuth appeared ( Figure 2f). [24][25][26] The areasofthe two peaks of metallicbismuth after 300-330 sw ere almostt he same as those after 90-120 s, as shown in Figures 2f and 2g.T his experiment was repeated several times and the resultswere always the same. The results indicated that defluorinationo ft he whole surface of an o-BiF 3 particle( or cluster) was almost completed within 120 s. The in- Ramans pectra taken at the position indicated by the blue arrowin(a).…”
Section: Resultsmentioning
confidence: 54%
“…The peak of o‐BiF 3 became smaller after 30–60 s (Figure e). After 90–120 s, the peak of o‐BiF 3 disappeared and two peaks of metallic bismuth appeared (Figure f) . The areas of the two peaks of metallic bismuth after 300–330 s were almost the same as those after 90–120 s, as shown in Figures 2 f and g. This experiment was repeated several times and the results were always the same.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, LIPSS have been proposed to be used in photonics, plasmonics, or even industrial applications such as micromachining, color marking, micro fluidic technologies and micro electromechanical systems [5][6][7]. Bismuth (Bi) is a very interesting material not only due to its thermal and electrical attributes, but also because of the optical properties of its nanostructured form [8,9]. In addition, Bi is found to be a versatile material in thin film laser processing [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Bi 2 O 3 has been generated in Bi with continuous wave (CW) or pulsed laser irradiation [10][11][12][13][14]. Also, the formation of LIPSS in Bi thin films by nanosecond pulsed laser irradiation was demonstrated in some prevoius work [8,9]. In that case, LIPSS created on the surface of the Bi film exhibited an orientation perpendicular to the laser polarization with periodicity on the order of the irradiation wavelength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation